Mapping Antibiotic-Resistant Neisseria Gonorrhoeae Isolates in Metropolitan Toronto: Issues of Scale, Positional Accuracy and Confidentiality - Jody F Decker; Bob Sharpe; Jo-Anne R Dillon (Canadian Journal of Infectious Diseases)
The primary objective of this paper was to investigate the methodological implications of mapping Neisseria gonorrhoeae using the partial three-digit postal code instead of the complete six-digit postal code. The reporting locations of N gonorrhoeae isolates submitted from hospitals, doctor’s offices, private and provincial laboratories, and sexually transmitted disease (STD) clinics were used as a model. Specifically, the paper focused on variations in geographical distributions of STD data when mapped at different aggregations of postal code data and at different map scales. Such variations are of importance to those who analyze the spatial epidemiology of STDs, and the accessibility and use of health care services. This analysis showed that three-digit postal codes are useful in summarizing overall geographic distributions, but greatly reduce positional accuracy, which can lead to inaccurate delineation of service areas and populations served. The six-digit postal code is more appropriate for detailed analysis addressing behavioural issues. The analysis demonstrated that six-digits can be used without breaching individual confidentiality.